Overexpression of Mn-superoxide dismutase in Oxya chinensis mediates increased malathion tolerance. (August 2017) - Wu, Haihua; Zhang, Yiwei; Shi, Xuekai; Zhang, Jianzhen; Ma, Enbo
Abstract: Superoxide dismutase (SOD) is the first line of defense against oxidative damage. Malathion is an organophosphate insecticide and can induce the production of reactive oxygen species (ROS) and cause the intracellular oxidative stress. The present study was undertaken to examine the effects of malathion on SODs activity and their transcriptional levels in Oxya chinensis (Thunberg) (Orthoptera: Acrididae). The results showed that total SOD and MnSOD activities increased as a dose-dependent manner while CuZnSOD activity has no significant changes after malathion treatments. Total SOD and MnSOD activities were the highest at the concentration of 0.8 μg μL −1 malathion treatment and increased significantly about 1.81- and 2.48-fold compared with the control, respectively. Increased mRNA expression of MnSOD, ecCuZnSOD1, and ecCuZnSOD2 were observed after malathion treatments. Moreover, the alteration of MnSOD transcript was similar to the profiles of MnSOD activity. These results suggested that the up-regulation expression of MnSOD transcript led to the increase of MnSOD activity in order to eliminate the excessive ROS caused by malathion. In addition, we evaluated the role of individual SOD gene in malathion stress by using RNAi and recombinant SOD proteins. The results showed that ROS contents increased significantly after the silencing of MnSOD and ecCuZnSOD1 genes. The OD values of the E. coli cells transformed with pET-28a-OcMnSOD plasmid were 1.13–1.31-fold and 1.08–1.33-fold higher than those of cells with pET-28a plasmids under 0.4 and 0.8 μg μL −1 malathion treatments, respectively. These findings indicated that MnSOD exerted an important role in defense oxidative stress caused by malathion. Graphical abstract: Highlights: Malathion increased total SOD and MnSOD activities in Oxya chinensis. Malathion induced the transcriptional levels of MnSOD, ecCuZnSOD1, and ecCuZnSOD2. The role of individual SOD gene was evaluated using RNAi and recombinant SOD proteins. MnSOD played an important role in defense oxidative stress induced by malathion.